1998
DOI: 10.1007/s004660050351
|View full text |Cite
|
Sign up to set email alerts
|

A meshless local boundary integral equation (LBIE) method for solving nonlinear problems

Abstract: A new meshless method for solving nonlinear boundary value problems, based on the local boundary integral equation (LBIE) method and the moving least squares approximation, is proposed in the present paper. The total formulation and a rate formulation are developed for the implementation of the present method. The present method does not need domain and boundary elements to deal with the volume and boundary integrals, which will cause some dif®culties for the conventional boundary element method (BEM) or the ®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(55 citation statements)
references
References 16 publications
0
53
0
1
Order By: Relevance
“…Recent works have indicated that highly accurate results may be obtained with meshless methods, as compared to grid-based methods [1,2]. Over the last years, several meshless methods have been proposed, as the Smoothed Particle Hydrodynamics (SPH) [3], the Diffuse Element Method (DEM) [4], the Element Free Galerkin method (EFG) [5], the Reproducing Kernel Particle Method (RKPM) [6,7], the Partition of Unity Finite Element method (PUFEM) [8], the h-p Clouds [9], the Moving Least-Square Reproducing Kernel method (MLSRK) [10], the meshless Local Boundary Integral Equation method (LBIE) [11], the Meshless Local Petrov-Galerkin method (MLPG) [12], meshless point collocation methods using reproducing kernel approximations [13], the Merhod of Fundamental Solutions (MFS) [14], the Method of Particular Solutions (MPS) [15] and more. In the present work we imply the MPC method for the solution of equations that describe the MHD flow.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have indicated that highly accurate results may be obtained with meshless methods, as compared to grid-based methods [1,2]. Over the last years, several meshless methods have been proposed, as the Smoothed Particle Hydrodynamics (SPH) [3], the Diffuse Element Method (DEM) [4], the Element Free Galerkin method (EFG) [5], the Reproducing Kernel Particle Method (RKPM) [6,7], the Partition of Unity Finite Element method (PUFEM) [8], the h-p Clouds [9], the Moving Least-Square Reproducing Kernel method (MLSRK) [10], the meshless Local Boundary Integral Equation method (LBIE) [11], the Meshless Local Petrov-Galerkin method (MLPG) [12], meshless point collocation methods using reproducing kernel approximations [13], the Merhod of Fundamental Solutions (MFS) [14], the Method of Particular Solutions (MPS) [15] and more. In the present work we imply the MPC method for the solution of equations that describe the MHD flow.…”
Section: Introductionmentioning
confidence: 99%
“…MLPG4 has been successfully applied to potential problems, elastostatics, elastodynamics, thermoelasticity, and plate bending problems [6,48,49,51,[53][54][55]68,69]. A summary of recent developments in the applications of MLPG4 can be found in [52].…”
Section: Applications Of the Mlpg Approachmentioning
confidence: 99%
“…There are many papers concerned with the numerical solutions of elliptic type boundary value problems by using the meshless and mesh reduction methods, such as Zhu et al, 1998Zhu et al, , 1999Zhu, 1998a, 1998b;Atluri et al, 1999;Atluri and Shen, 2002;Li et al, 2007 andGhimire et al, 2016. The collocation techniques together with the expansion of trial solutions by utilizing different basis-functions were employed to solve the elliptic type boundary value problems; see, for example, Cheng et al, 2003;Hu et al, 2005;Tian et al, 2008, and Hu and Chen, 2008.…”
Section: Introductionmentioning
confidence: 99%